2014
DOI: 10.1016/j.apmr.2013.08.235
|View full text |Cite
|
Sign up to set email alerts
|

Standing Data Disproves Biomechanical Mechanism for Balance-Based Torso-Weighting

Abstract: Objective To test a proposed mechanism for the effect of Balance-Based Torso-Weighting (BBTW) in people with multiple sclerosis and healthy controls. The application of light weights to the trunk may result in a biomechanical shift of postural sway in the direction of weighting, mechanically facilitating maintenance of center of mass over the base of support. Design Non-randomized controlled trial Setting motion analysis laboratory Participants 20 participants with multiple sclerosis (average EDSS 4.1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Torso-weighting differs from the traditional rehabilitative method of placing heavier weights at the trunk or limbs to help control movement 21 because it uses light weights, generally less than 2% of body weight, strategically placed based on evidence of imbalance or asymmetry of response. 19 Previous work has shown that immediately after torso-weighting, people with MS have improved static stability with decreased sway when standing with eyes open and closed, 5,20 increased ability to resist rotational forces while standing, 5 and more optimized variability of postural sway. 22 Torso-weighting has resulted in improved dynamic stability in sit-to-stand transfers and walking 20 and in increased gait velocity, cadence, and percentage of gait cycle spent in single-limb support in people with MS. 23 However, to our knowledge, the effect of torsoweighting on falls in people with MS has not yet been studied.…”
Section: Effects Of Torso-weighting On Balance and Fallsmentioning
confidence: 99%
See 3 more Smart Citations
“…Torso-weighting differs from the traditional rehabilitative method of placing heavier weights at the trunk or limbs to help control movement 21 because it uses light weights, generally less than 2% of body weight, strategically placed based on evidence of imbalance or asymmetry of response. 19 Previous work has shown that immediately after torso-weighting, people with MS have improved static stability with decreased sway when standing with eyes open and closed, 5,20 increased ability to resist rotational forces while standing, 5 and more optimized variability of postural sway. 22 Torso-weighting has resulted in improved dynamic stability in sit-to-stand transfers and walking 20 and in increased gait velocity, cadence, and percentage of gait cycle spent in single-limb support in people with MS. 23 However, to our knowledge, the effect of torsoweighting on falls in people with MS has not yet been studied.…”
Section: Effects Of Torso-weighting On Balance and Fallsmentioning
confidence: 99%
“…The nonweighted testing always preceded the weighted testing because people have shown carryover effects of the Balance-Based Torso-Weighting for hours after the weights have been removed. 5,20 Disease Steps 24 was rated by a single researcher (G.L.W.) during the first set of clinical tests.…”
Section: Torso-weighting Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a weight placed anteriorly to the left may counter inability to hold against a rotational force at the pelvis. The mechanism for the effect of BBTW is unknown, although sensory augmentation may play a role because people do not mechanically shift in the direction of weighting (Crittendon et al, 2014). Previous research has shown promising results.…”
Section: Introductionmentioning
confidence: 99%